The Role of Change Leaders in Improving The Performance of Public Organizations - Enadarlita Enadarlita; Muhammad Dianto; Sultoni Sultoni (Jurnal Prajaiswara, 2020)
In an organization, performance assessment is very important because this assessment can be used as a measure of the success of the organization within a certain period. The assessment can be used to improve or enhance the performance of the organization concerned. Government organizations are public organizations that aim to meet the needs and interests of the public, so the performance of these public organizations can only be said to be successful if they can realize their goals and mission. The success of an organization in improving its performance cannot be separated from the role of a leader, especially a change leader. A successful leader is an l leader who can mobilize aspects of input or resources, such as employees, budgets, facilities and infrastructure; information; and organizational culture. As well as those relating to the management process, planning, organizing, implementation, budgeting, supervision, and evaluation.